Lateral impact response of circular hollow steel tubes with mid-span localized penetrating notches - Huang, Xiaoli; Wang, Yulin (Frontiers in Materials, 2023)
In this study, 32 numerical models of CHST columns were established in the ABAQUS program to evaluate the effect of mid-span local defects on the impact resistance of circular hollow steel tube (CHST) columns. The simulation studies were conducted from three aspects: notch length, notch angle, and impact energy. The results showed that under a lateral impact load, the mid-span of the CHST column presented global bending failure patterns accompanied by local indentation deformation in the impact region and local buckling deformation at the bottom of the fixed end. Compared with the mid-span indentation displacement of the non-notch model, when the impact velocities were 30km/h and 60km/h, the horizontal notch model surpassed the maximum by 29.3% and 36.3%, the oblique notch model surpassed the maximum by 47.8% and 115.6%, and the vertical notch model only increased by 9.7% and 1.1%. The local damage area and impact force time-history curves of the vertical notch model agreed well with those of the non-notch model. Among the three notch angles, the impact plateau values of the vertical notch model and the global bending displacement in the mid-span were least affected by the notch length, notch location, and impact energy. The energy absorption of the CHST column was mainly due to indentation deformation in the mid-span, and the global bending deformation was auxiliary. Compared with the energy absorption ratio (EAR) of the non-notch model, with increased impact energy, the EAR of the vertical notch model increased by 20.2%, 13.5%, and 17.3% on average. The horizontal and oblique notch models decreased by 28.2%, 61.0%, 42.4%, and 29.1%, 62.7%, and 49.3%, respectively. The Rd of all notch models showed an overall upward trend as the impact energy increased, and the Rd of the horizontal notch model increased the most. According to the parametric analysis results, the dynamic flexural capacity prediction formula of the CHST columns section was obtained, considering the influence of notch length, notch angle, and impact energy within the parameter range of this study.